The Colour Revolution: Disney, DuPont and Faber Birren (Cinéma & Cie. Film and Media Studies Journal, 2019)
This paper explores the professional cross-connections between the Walt Disney studios, who pioneered the early adoption of Technicolor IV, DuPont, whose chemical research provided the colour pigments and Pyralin cels used in Disney’s films, and Faber Birren, one of the most influential corporate American consultants in colour design and marketing. It considers several aspects of colour that have not previously been considered in colour or animation studies: first, the material history of cellulose nitrate and acetate and its structural and aesthetic relationship to colour and transparency in animation; second, the role that colour paints and pigments developed by the DuPont company played as part of its targeting of Hollywood as a strategic new market, and third, the ways in which colour production was aesthetically informed by colour consultants like Birren across multiple realms, from cinema to interior design and architecture. By considering how colour production and design was situated within larger corporate strategies at DuPont in which colour was key to its industrial and consumer markets, I hope to enrich our understanding of the role that Disney, DuPont and Faber Birren played in the colour revolution of the mid-twentieth century.